OBSERVATORIES AND ASTRONOMIC ALIGNMENTS IN THE INCA TAMPU OF HUANUCO PAMPA - Pino Matos, José Luis (2004)
The archaeological site of Huánuco Pampa, one of the best designed Inka tampus in the Central Andes during the expansion of the Tawantinsuyu Empire, shows evidences of significant astronomical alignments associated to main spaces and buildings. They can be observed at the “Ushnu” platform and the “Inkawasi”; among the “Tianas” (stone seats), niches and main doorways of both of the two structures built of fine Inka masonry. These alignments are associated to positions of the Sun in the equinox, zenith, antizenith and solstices; alignments of the Moon in their extreme positions; as well as very specific star positions of Alpha and Beta Centaurus and the Southern Cross. With these evidences, we propose the importance of the use of the Inka Astronomy in the provincial centers.